2021
DOI: 10.1007/s11912-021-01057-3
|View full text |Cite
|
Sign up to set email alerts
|

Locally Advanced Pancreatic Cancer: Percutaneous Management Using Ablation, Brachytherapy, Intra-arterial Chemotherapy, and Intra-tumoral Immunotherapy

Abstract: Purpose of Review Pancreatic ductal adenocarcinoma (PDAC) is one of the most aggressive neoplasms, bearing a terrible prognosis. Stage III tumors, also known as locally advanced pancreatic cancer (LAPC), are unresectable, and current palliative chemotherapy regimens have only modestly improved survival in these patients. At this stage of disease, interventional techniques may be of value and further prolong life. The aim of this review was to explore current literature on locoregional percutane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 113 publications
(135 reference statements)
0
9
0
Order By: Relevance
“…Iodine-125 ( 125 I) seed implantation is a type of brachytherapy or interventional radiotherapy that has been used in the treatment of pancreatic neoplasm for decades. Because 125 I seeds can be placed directly within the tumor and have a small radiation radius, a high radioactive dose can be used to kill nearby tumor cells without causing significant collateral damage to surrounding tissues [41]. Pancreatitis, fistulas, seed migration, ulcers, infections, leaks, and intestinal perforations are the most common (significant) consequences of percutaneous 125 I seed implantation [42].…”
Section: Discussionmentioning
confidence: 99%
“…Iodine-125 ( 125 I) seed implantation is a type of brachytherapy or interventional radiotherapy that has been used in the treatment of pancreatic neoplasm for decades. Because 125 I seeds can be placed directly within the tumor and have a small radiation radius, a high radioactive dose can be used to kill nearby tumor cells without causing significant collateral damage to surrounding tissues [41]. Pancreatitis, fistulas, seed migration, ulcers, infections, leaks, and intestinal perforations are the most common (significant) consequences of percutaneous 125 I seed implantation [42].…”
Section: Discussionmentioning
confidence: 99%
“…Timmer et al reported the most interesting studies in this field applied to pancreatic cancer [ 66 ].…”
Section: Loco-regional Therapiesmentioning
confidence: 99%
“…Compared with other thermal ablation techniques, MWA can rapidly heat tissue and is insusceptible to the heat sink effect. [ 145 , 146 ] However, akin to RFA, MWA is usually used as a single treatment, accompanied with the postoperative tumor recurrence rate remaining high, and the prognosis is unsatisfactory. Therefore, it is necessary to develop new solutions to overcome these concerns.…”
Section: Clinical Physiotherapy‐activated or Combined Immunotherapymentioning
confidence: 99%